2017
DOI: 10.1038/s41598-017-15505-3
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from MSCs activates dermal papilla cell in vitro and promotes hair follicle conversion from telogen to anagen in mice

Abstract: Hair loss is a common medical problem. In this study, we investigated the proliferation, migration, and growth factor expression of human dermal papilla (DP) cells in the presence or absence of treatment with mesenchymal stem cell extracellular vesicles (MSC-EVs). In addition, we tested the efficacy of MSC-EV treatment on hair growth in an animal model. MSC-EV treatment increased DP cell proliferation and migration, and elevated the levels of Bcl-2, phosphorylated Akt and ERK. In addition; DP cells treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 75 publications
(77 reference statements)
8
115
0
Order By: Relevance
“…In addition to the present study, three groups have recently reported that EVs derived from either MSCs or DPCs activated β‐catenin and/or sonic hedgehog pathways in vitro and HF growth in vivo through telogen reactivation . It confirms that EVs participate to the cell–cell communications that occur during HF physiology and cycling.…”
Section: Resultssupporting
confidence: 85%
“…In addition to the present study, three groups have recently reported that EVs derived from either MSCs or DPCs activated β‐catenin and/or sonic hedgehog pathways in vitro and HF growth in vivo through telogen reactivation . It confirms that EVs participate to the cell–cell communications that occur during HF physiology and cycling.…”
Section: Resultssupporting
confidence: 85%
“…The conditioned medium secreted by stem cells also act as a highly enriched source of growth factors that stimulates hair growth. The hair growth promoting effects of stem cells and conditioned medium have been mediated via activation of DPCs .…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%
“…Maintenance of anagen, in contrast, is controlled by insulin-like growth factor-1, hepatocyte growth factor, and vascular endothelial growth factor (VEGF) [54]. As anagen progresses, the bulge reverts to a Wnt-inhibited state [55], and Wnt inhibition by TCF3, Wnt inhibitory factor 1 and Dkks (e.g., Dkk3) and the calcium-dependent transcription factor NFATc1 [56] maintain bulge stem cells in a quiescent state [7].…”
Section: Anagenmentioning
confidence: 99%